(untitled) (Scientific journal of the Fergana State University, 2025)
In this article presents, the results of a study of the mineral composition of the skin, wool, liver, kidneys and heart of a rabbit grown in the Fergana region using optical emission spectrometry with inductively coupled plasma. Based on the analysis, the amount of 21 elements in the skin and liver, kidneys and heart and 20 elements in wool out of 30 studied elements was determined. Rabbit liver, kidney, and heart were found to be rich in macronutrients, with 1.58 times more macronutrients than skin and 2.65 times more than fur. Of the macroelements, phosphorus, potassium and magnesium were found in the liver, kidneys and heart of the rabbit, sodium in the skin, and sulfur and calcium in wool. Of the microelements, lithium, boron, aluminum, silicon, vanadium, chromium, manganese, iron were found. cobalt, nickel, copper, zinc, strontium and molybdenum. It was shown that the iron content in the liver, kidneys and heart of the rabbit was 1.86-1.97 times higher than in the other samples, and the amount of zinc in the wool was 7.6-8 times higher. Among the toxic elements, only cadmium was found in small quantities in the studied samples.